ChemInform Abstract: Amino Group Immobilized on Polyvinyl Alcohol as a Reusable Catalyst for Highly Accelerated N‐Formylation of Amines Using Formic Acid under Solvent‐Free Condition. Issue 21 (6th May 2016) - Rezazadeh, Soodabeh; Akhlaghinia, Batool
Abstract: The catalyst can be reused up to four times without significant loss of activity.